HUBUNGAN TINGKAT SPIRITUALITAS DENGAN PSYCHOLOGICAL DISTRESS PADA KELUARGA PASIEN DI UNIT PERAWATAN INTENSIF - Ningsih, Yofilia (Jurnal Keperawatan Profesional, 2024)
Intensive care units often become stressful environments where families of patients experience emotional impacts due to serious health conditions, and spirituality serves as an effort to cope with psychological discomfort. The research aims to examine the correlation between the level of spirituality and psychological distress in the families of patients. This is a non-experimental quantitative study using a correlational approach with a cross-sectional method. The research was conducted at Arifin Achmad Hospital in Pekanbaru. Sample selection was done using accidental sampling, considering inclusion and exclusion criteria, resulting in 40 respondents. The measurement tools used were the Daily Spiritual Experience Scale (DSES) questionnaire and the Hospital Anxiety and Depression Scale (HADS) questionnaire. Data analysis employed the Chi-Square test with α = 0.05. The research results indicate a description of a high level of spirituality in 67.5% of the respondents. The description of psychological distress is moderate in 40% of the cases. The Chi-Square statistical test yielded a p-value of 0.000 (p < 0.05). In conclusion, there is a relationship between the level of spirituality and psychological distress in the families of patients in the intensive care unit, indicating that families with lower levels of spirituality are more susceptible to experiencing severe psychological distress when facing high-stress situations.